Implementation of the Policy Support Instrument. (Policy Papers; Policy Paper ;, 2005)
Within the terms of the proposed decisions, staff has formulated specific proposals on a number of issues raised in general terms during the previous Board discussion: (i) the modalities for a fixed schedule of reviews, including how to signal that a program is back on track; (ii) the application of a misreporting framework under the PSI; and (iii) the relationship between the PSI and the PRS process.